Unphysical nucleation of diamond in the extended cutoff Tersoff potential - Aghajamali, Alireza; de Tomas, Carla; Suarez-Martinez, Irene; Marks, Nigel (Taylor & Francis, 2018)
In simulations of carbon materials it is common practice to view the coefficients of the cutoff function as free parameters which can be optimised according to the system of interest. This work examines a common modification to the widely used Tersoff potential in which the coefficient of the upper cutoff is increased to improve the properties of amorphous carbon. Using molecular dynamics simulations, we show that this so-called extended cutoff Tersoff model leads to nucleation of diamond nanocrystals during annealing of amorphous carbon. By varying the density of the system, and examining the radial distribution function in conjunction with the modified cutoff function, we demonstrate that this behaviour is unphysical, and does not represent a new pathway for synthesising diamond. Viewed from a broader perspective, this observation provides a cautionary tale against altering the parameters of empirical potentials without fully considering the wider implications.